Biogenic Nanosilver Mediated by Coir, Medicinal Plant Extracts and their Antimicrobial Validation - Kanagaraju, Geethanjali; Sebastian, Sumy; Ravindranath, Anita Das (International Coconut Community, 2017)
Knowing the magnitude of therapeutic plants such as Micrococca mercurialis (MM), Abutilon palmeri (AP) and Callistemon citrinus (CC), we also planned to extend our research work on Cocusnucifera fibers (CF) and dust (CD) as it has copious medicinal properties. The current study deals with the green synthesis of silver nanoparticles (AgNPs) from fresh aqueous extracts and AgNO3 solution. The biogenic conversion of silver ion to silver is relatively expeditious at two different time intervals and pH. The isolated silver nanoparticles (AgNPs) from the bio extracts were identified initially by scrutinizing the colour variations. The biosynthesized AgNPs were characterized by UV, XRD, Laser Diffraction Particle size Analyser, fluorescence spectroscopy, SEM and TEM. UV absorbance at 435-460nm for silver nanoparticles was observed for the above extracts. The XRD pattern of all extracts showed the distinctive Bragg peaks of face centre cubic (fcc) crystalline system available in nature. SEM and TEM analysis of the silver nanoparticles indicated that the particle size was in the range of 2-100nm with polygonal and spherical shapes. The biosynthesized AgNPs were evaluated for antimicrobial activities. The CFAgNPs showed an efficient antibacterial activity at lower concentration (25mg/ml) against Pseudomonas demolytica followed by Staphylococcus aureus and Escherichia coli. Similarly all plant extracts have better activity against fungal strains. It is concluded that the biogenic blend of AgNPs is simple, extremely rapid, beneficial, eco-friendly and more stable without any toxic effects. Of these, CFAgNps may be used for the preparation of antibacterial groupings against Pseudomonas demolytica and Staphylococcus aureus.